The Influence of Education About Cervical Cancer Through Online Meeting on The Knowledge of Adolescent Women - Sandriani Sandriani; Yanti Srinayanti; Rosidah Solihah; Iin Marlina (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: Cervical cancer ranks first after breast cancer in developing countries, the only one being Indonesia. Cervical cancer is a sexually transmitted disease that originates from an infectious virus, namely the human papilloma virus, which triggers changes in the behaviour of cervical epithelial cells. Reproductive health problems faced by women today are increasing infections in the reproductive organs, eventually causing cancer. The prevalence of women with cervical cancer is high due to their tendency to marry at a young age and their limited economic capacity, which limits their access to information. Provision of health education through Zoom meetings, considering the limitations due to the pandemic, really needs to be done for adolescents as a preventive effort considering that teenagers are very vulnerable to having free sex. Objective: The effect of education through a zoom meeting on cervical cancer on the knowledge of young women in SMA Negeri 1 Lumbung in March 2022. The research used is a quantitative study. Method: The research used is a quantitative study. A tool for data collection using a questionnaire while the total sampling technique with a sample of 40 students. Result: The results of data analysis using a t-test on the effect of education through zoom meetings on cervical cancer obtained a significant value because the value of t count > t table = 15,627 > 2,023 and the value of > p value = 0.05 > 0.000. Conclusion: From the results of the study, it can be concluded that there is a significant effect of health education between before being given health education and after being given health education.